Original paperNocturnal Electrobioimpedance Volumetric Assessment (NEVA®): an alternative for determining the quality of nocturnal erections - Michielsen, Dirk P.J.; Amy, Jean-Jacques (Archives of Medical Science, 2005)
Objectives: The NEVA® device (Urometrics, Inc) measures changes in penile blood flow during nocturnal erections and enables one to make the diagnosis of either arterial insufficiency or venous leakage. The RigiScan® (Osbon Medical Systems) determines the quality of nocturnal erections to establish the organic or psychogenic nature of erectile dysfunction (ED) without indicating the nature of the impotence. This study compares both devices and tries to answer two questions. Does NEVA® give information on nocturnal erections comparable to that provided by the RigiScan®? What is the diagnostic capacity of NEVA® when compared to a comprehensive approach including laboratory examinations, psychological evaluation, intra-cavernous injection, and Duplex Doppler? Material and methods: Twenty-five men with complaints of ED were enrolled in our study. Each of them had a complete work-up. This included the use of the RigiScan® for two consecutive nights. Then the NEVA® and RigiScan® devices were used simultaneously for the third night. The dynamic data provided by the NEVA® system were compared to the conventional nocturnal penile tumescence testing by means of the RigiScan®. Results: An analysis of all sessions shows that all night recordings are comparable. The mean number of erections/night (2.80±0.34 vs 2.76±0.31) does not differ statistically significantly between NEVA® and RigiScan® assessments. Also the mean duration of events (30.66±1.92 minutes vs 25.63±1.62 minutes) does not differ. Normal axial rigidity by NEVA® (>200% change over baseline) correlates with all grade III erections by RigiScan®. The analysis of NEVA® data gives in 84% of the cases the same diagnosis of ED as that made after a complete work-up. Conclusions: The present study demonstrates that electrobioimpedance registration has a good correlation with conventional penile tumescence testing. The analysis of data obtained with the NEVA® device seems to be an important and easy method for predicting the etiology of ED. For the assessment of the performance of the male partner during a sexual intercourse the registration of axial rigidity is a more important parameter than radial rigidity.